Artificial penile nodules and secondary syphilis. Issue 3 (June 1991) - Wolf, P; Kerl, H
Abstract : A patient with artificial penile nodules and ulcerative plaques on the penis is described. Clinical course, histology and serological examination revealed a diagnosis of secondary syphilis. The differential diagnosis of the ulcerative genital lesions in the presence of artificial penile nodules is discussed.